Two-dimensional 1H NMR study of the lambda operator site OL1: a sequential assignment strategy and its application. - Weiss, M A (1984)
The solution structure and dynamics of the 17-base-pair synthetic operator site OL1, which is recognized by the cI and Cro repressors of bacteriophage lambda, is studied by two-dimensional NMR methods. A sequential assignment strategy for nucleic acids is proposed and illustrated by the assignments of the base and sugar protons of OL1.